Field assessment of blackgram (Vigna mungo L. Hepper) genotypes against major insect pests in subtropical region of Nepal - Neupane, Saraswati; Subedi, Subash; Darai, Rajendra; Sharma, Trista (Journal of Agriculture and Natural Resources, 2021)
Direct damage due to insect pests is one of the major causes limiting the yield potential of blackgram (Vigna mungo L. Hepper) in Nepal. A total of 17 blackgram genotypes were screened for resistance to major insect pests, including aphid (Aphis craccivora Koch.), whitefly (Bemisia tabaci Genn.), hairy caterpillar (Spilosoma obliqua Walker) and pod borer (Helicoverpa armigera Hubner) in National Maize Research Program, Rampur, Chitwan during summer season of 2018 and 2019. The design of the experiment was randomized complete block having three replications. Genotypes were sown on first week of August in a unit plot size of 4 rows of 2 m long with 40 cm row to row spacing and continue plant to plant spacing was maintained and net harvested plot was 3.2 square meters. The recommended dose of fertilizer was 20:40:20 N:P2O5:K2O kg/ha and seed rate 25 kg/ha. The package of agronomic practices was followed as per national recommendation. Data on insects were collected by counting the number of insects per plant. The yield and yield components were recorded at harvest. All screened genotypes differed significantly (p<0.05) for insect population, yield and yield components. From two years field data, three genotypes BLG0069-1, BLG0036-1 and BLG0079-1 had lower number of above mentioned insect populations, exhibited more resistant in both years and produced higher grain yield ( 1.5 t/ha) than other genotypes. These genotypes might be useful for the development of major insect pest tolerant high yielding blackgram variety in subtropical region of Nepal.